Relationship between the Expression of Matrix Metalloproteinases and Their Tissue Inhibitors in Patients with Brain Tumors - Dibdiakova, Katarina; Majercikova, Zuzana; Galanda, Tomas; Richterova, Romana; Kolarovszki, Branislav; Racay, Peter; Hatok, Jozef (International journal of molecular sciences, 2024)
Matrix metalloproteinases (MMPs) and their inhibitors (TIMPs) play critical roles in regulating processes associated with malignant behavior. These endopeptidases selectively degrade components of the extracellular matrix (ECM), growth factors, and their receptors, contributing to cancer cell invasiveness and migratory characteristics by disrupting the basal membrane. However, the expression profile and role of various matrix metalloproteinases remain unclear, and only a few studies have focused on differences between diagnoses of brain tumors. Using quantitative real-time PCR analysis, we identified the expression pattern of ECM modulators (n = 10) in biopsies from glioblastoma (GBM; n = 20), astrocytoma (AST; n = 9), and meningioma (MNG; n = 19) patients. We found eight deregulated genes in the glioblastoma group compared to the benign meningioma group, with only MMP9 (FC = 2.55; p = 0.09) and TIMP4 (7.28; p < 0.0001) upregulated in an aggressive form. The most substantial positive change in fold regulation for all tumors was detected in matrix metalloproteinase 2 (MNG = 30.9, AST = 4.28, and GBM = 4.12). Notably, we observed an influence of TIMP1, demonstrating a positive correlation with MMP8, MMP9, and MMP10 in tumor samples. Subsequently, we examined the protein levels of the investigated MMPs (n = 7) and TIMPs (n = 3) via immunodetection. We confirmed elevated levels of MMPs and TIMPs in GBM patients compared to meningiomas and astrocytomas. Even when correlating glioblastomas versus astrocytomas, we showed a significantly increased level of MMP1, MMP3, MMP13, and TIMP1. The identified metalloproteases may play a key role in the process of gliomagenesis and may represent potential targets for personalized therapy. However, as we have not confirmed the relationship between mRNA expression and protein levels in individual samples, it is therefore natural that the regulation of metalloproteases will be subject to several factors.